2015
DOI: 10.1186/s12909-015-0455-6
|View full text |Cite
|
Sign up to set email alerts
|

A little healthy competition: using mixed methods to pilot a team-based digital game for boosting medical student engagement with anatomy and histology content

Abstract: BackgroundDigital games have been demonstrated to be beneficial for a range of non-recreational purposes, with a particular focus on their value for education. There is a limited amount of research supporting their use for medical education, but their are several studies on their use in areas such as surgical training, and life-support re-training. However, a significant gap exists in demonstrating how they engage with learners and games can be used most effectively in medical education. This pilot study asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 13 publications
2
39
0
1
Order By: Relevance
“…Promoting game-based learning can support medical student engagement with anatomy and the findings of this study are consistent with the literature on digital games and their use as a tool for fun and engagement in education (Griffiths, 2002;Anyanwu, 2014;Janssen, 2015). In our study, the observed classroom environment benefits can be listed as higher attendance and participation, and more focused and engaged students in class.…”
Section: Discussionsupporting
confidence: 79%
“…Promoting game-based learning can support medical student engagement with anatomy and the findings of this study are consistent with the literature on digital games and their use as a tool for fun and engagement in education (Griffiths, 2002;Anyanwu, 2014;Janssen, 2015). In our study, the observed classroom environment benefits can be listed as higher attendance and participation, and more focused and engaged students in class.…”
Section: Discussionsupporting
confidence: 79%
“…They have shown preference to 'ubiquitous learning' in which imbibing knowledge is dispersed in time and space (Burbules, 2012). Several studies (Dennen & Hao;Janssen et al, 2015) have shown similar student interest in ELR while other studies like Johnson et al) reported less use of oral histology course website.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown considerable interest in integrating games and digital technologies into educational activities. Studies claim that game‐based learning provides more engagement for the learner, allows personalized learning opportunities, teaches important technical skills, and creates an environment for relevant assessment . Challenges imposed by game‐based learning encourage and reinforce thinking, planning, and technical skills.…”
Section: Discussionmentioning
confidence: 99%